VAT Fraud and Evasion : What Do We Know, and What Can be Done? - Smith, Stephen (IMF Working Papers; Working Paper ;, 2007)
Like any tax, the VAT is vulnerable to evasion and fraud. But its credit and refund mechanism does offer unique opportunities for abuse, and this has recently become an urgent concern in the European Union (EU). This paper describes the main forms of noncompliance distinctive to a VAT, considers how they can be addressed, and assesses evidence on their extent in high-income countries. While the practical significance of current difficulties in the EU should not be over-stated, administrative measures alone may prove insufficient to deal with them, and a fundamental redesign of the VAT treatment of intra-community trade required. The current difficulties in the EU largely reflect circumstances that would not apply in the United States.